Functional and Visual Acuity Outcomes of Cataract surgery in Timor-Leste (East Timor). (December 2014) - Naidu, Girish; Correia, Marcelino; Nirmalan, Praveen; Verma, Nitin; Thomas, Ravi
Abstract Purpose: To report functional outcomes following cataract surgery in Timor-Leste. Methods: Pre- and post-intervention study measuring visual function improvement following cataract surgery. Presenting visual acuity (VA) was measured and visual function documented using the Indian vision function questionnaire (IND-VFQ). Results: All 174 persons undergoing cataract surgery from November 2009 to January 2011 in Timor-Leste were included. Mean age was 65.4 years; 113 (64.9%) were male, 143 (82.1%) were from a rural background and 151 (86.8%) were illiterate. Pre-operatively, 77 of 174 patients (44.3%, 95% confidence interval, CI, 37.0–51.7%) were blind (VA ≤3/60), 77 (44.3%, 95% CI 37.0–51.7%) were visually impaired (VA <6/18–>3/60), while 20 (11.5%, 95% CI 7.4–16.9%) had presenting acuity ≥6/18 in the better eye. Following surgery, significant improvement in visual function was demonstrated by an effect size of 2.8, 3.7 and 3.9 in the domains of general functioning, psychosocial impact and visual symptoms, respectively. Four weeks following surgery, 85 patients (48.9%, 95% CI 41.5–66.3%) had a presenting VA ≥6/18, 74 (42.5%, 95% CI 35.3–45.9%) were visually impaired and 15 (8.6%, 95% CI 5.0–13.6%) were blind. IND-VFQ improvement occurred even in patients remaining visually impaired or blind following surgery. Conclusion: In this setting, cataract surgery led to a significant improvement in visual function but the VA results did not meet World Health Organization quality criteria. IND-VFQ results, although complementary to clinical VA outcomes did not, in isolation, reflect the need to improve program quality.